GENETIC VARIABILITY AND HERITABILITY ANALYSIS FOR SOME QUANTITATIVE TRAITS IN FIELD PEA (PISUM SATIVUM L.) - RAVI RANJAN SAXESENA,; VIDYAPATI VIDYAKAR,; MANISH K. VISHWAKARMA,; PUNAM S. YADAV,; MOHAN LAL MEENA,; G. M. LAL, (The Bioscan, 2014)
To best exploit the available genetic wealth in the crop, the information on the nature and degree of diversity in the genotypes is crucial. Twenty one advanced breeding lines along with two commercial varieties (HUDP 15 and IPFD 1-10) as check were evaluated for assessing genetic variability and heritability for eleven different quantitative characters. The mean sums of squares due to advanced breeding lines were highly significant for all of the characters. The estimates of GCV and PCV were high for plant height (24.58, 25.17), whereas moderate for yield per plant (18.40, 19.58), number of clusters per plant (17.61, 20.31) and number of pods per plant (15.12, 19.24). High heritability coupled with high genetic advance was recorded for plant height (95.00, 33.72), moderate for days to 50% flowering (95.00, 14.85) and high heritability coupled with low genetic advance was observed for yield per plant (88.00, 3.81) and 100 seed weight (70.00, 2.95). Based on Per se performance for seed yield per plant and other characters taken in to consideration advanced breeding line FP8-242 was found best performer.